(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
The law guarantees compulsory schooling for young people with intellectual disabilities, either through the inclusive route or through the special route. But once it has been overcome, until very recently there were no training alternatives that allowed them to continue forming and, especially, to choose their vocation. In front of this excluding reality to this group, the Pontifical Comillas University started seven years ago DEMOS Training Programs, focused on providing high work skills adjusted to the needs of the working market and, the most important thing, to allow them to develop their vocation.